ANALISIS DEIKSIS DALAM NOVEL “SKAYA AND THE BIG BOSS” KARYA MARSELLA TINA: PERSPEKTIF PRAGMATIK GEORGE YULLE - Hasun, Moh; Hodairiyah; Asmoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the types of deixis and thoroughly analyze the intended meaning of utterances within the dialogue of the novel *Skaya and The Big Boss* by Marsella Tina, utilizing George Yule’s pragmatic framework. The research employs a qualitative descriptive approach, specifically a library-based case study method. The data focuses on character-to-character utterances containing elements of personal, spatial (place), and temporal (time) deixis. Data collection utilized library research techniques integrated with listening methods, specifically the basic